Perilaku Keuangan Pemilik UKM dalam Mengakses Produk Bank Syariah: Akad Pembiayaan Mudharabah Variabel Moderasi - Sujana, Duduh; Hidayat, Ahmad (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The Small and Medium Enterprises (SMEs) sector plays an important role in the Indonesian economy, which is the driving force for the economy. The 2016-2020 period, the average growth in financing for SMEs grew by 5.9% per year with the aim of working capital and investment growing by 4.85% and 8.15% per year, however, the portion of SME financing to the total financing carried out by Islamic banks experienced downward trend. The aim of the study was to determine the financial behavior of SME owners in accessing Islamic banking products with a Mudharabah financing contract with a moderating variable. The research variable is financial behavior which includes attitudes, subjective norms and behavior control and access to Islamic bank products and Mudharabah contracts as moderating variables. The object of research includes SMEs in the Sumedang area of West Java in the entire population of Sumedang SMEs where the sampling technique is through purposive sampling of 80 respondents. Qualitative descriptive research method with triangulation techniques. The results showed that all research variables obtained good results, meaning that access to Islamic bank products is supported by SME financial behavior while the development of Islamic banking literacy that strengthens SME financial behavior decisions needs to be improved and mudharabah financing contracts need to be given access to improve SME performance through financing sharia products.